2004
DOI: 10.1111/j.1365-2052.2004.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Native antiviral specificity of chicken Mx protein depends on amino acid variation at position 631

Abstract: An attempt was made to determine whether amino acid variation at position 631 in the chicken Mx protein definitely influences antiviral specificity, using an artificial mutation technique by which a single amino acid was reciprocally substituted between Ser (AGT) and Asn (AAT) at position 631 of the negative and positive chicken Mx, respectively. Using permanently transfected 3T3 cell lines, the antiviral potential of chicken Mx against vesicular stomatitis virus infection was analysed. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 23 publications
1
57
1
Order By: Relevance
“…The Mx system, which was shown to be important in mammalian cells, may be operative in chickens but only infrequently, being restricted to those few birds that have a unique amino acid change in the Mx protein (20). Two other reactants that avian cells produce following virus infection may also contribute to the reduction of virus shedding in AIV-infected chickens: ChIFN-␥ (6, 61), with its capacity to act synergistically with ChIFN-␣ (46), and a secreted dsRNase unique to avian species and coinduced with IFN (34).…”
Section: Discussionmentioning
confidence: 99%
“…The Mx system, which was shown to be important in mammalian cells, may be operative in chickens but only infrequently, being restricted to those few birds that have a unique amino acid change in the Mx protein (20). Two other reactants that avian cells produce following virus infection may also contribute to the reduction of virus shedding in AIV-infected chickens: ChIFN-␥ (6, 61), with its capacity to act synergistically with ChIFN-␣ (46), and a secreted dsRNase unique to avian species and coinduced with IFN (34).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive expression of the Mx allele in 3T3 cell lines from a Japanese Shamo (SHK) line of chickens resulted in a 10-to 100-fold reduction in influenza virus titers (14). Certain chicken Mx proteins have also been shown to inhibit replication of vesicular stomatitis virus (VSV) (14), and artificial mutation has demonstrated that the amino acid at position 631 of the chicken Mx protein is a crucial determinant of anti-VSV activity (Asn631 is active and Ser631 is inactive against VSV) (15). SHK Mx also has an Asn residue at position 631, and it has been inferred that this polymorphism is important for anti-influenza activity.…”
Section: Proteins Are Interferon (Ifn)-induced Dynamin-likementioning
confidence: 99%
“…However, multiplex real time allele specific PCR employed in the current study demonstrated by Ye et al (2010) is simple, robust and effective method for large scale screening. Genotype A at position 2032 corresponds to the asparagine aminoacid at position 631 of Mx protein and has higher antiviral activity than serine aminoacid coded by G at position 2032 (Ko et al, 2004). Thus, genotype A is considered as resistant allele and G as susceptible allele (Seyama et al, 2006;Watanabe, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Different alleles of chicken Mx gene have been shown to vary in their antiviral activity against influenza virus in an in vitro infection study and recombinant vesicular stomatitis virus (Bernasconi et al, 1995;Ko et al, 2002). A non-synonymous mutation at position 2032 of chicken Mx gene responsible for variation of aminoacid (Ser to Asn) in protein has been demonstrated to be responsible for negative to positive antiviral activity of Mx protein (Ko et al, 2002(Ko et al, , 2004. Recently this SNP have been demonstrated to confer more resistance in chicken to in vivo experimental infection of highly pathogenic avian influenza virus (HPAIV) (Ewald et al, 2011, Wang et al, 2012, Fulton et al, 2014.…”
Section: Introductionmentioning
confidence: 99%